Implementation of the Proposed DPOAE Estimation Technique - Rahil, Harpreet Singh (My University, 2007)
Implementation of the proposed DPOAE estimation technique is presented A new method of measurement of distortion product otoacoustic emission (DPOAE) signal level based on a recently introduced nonlinear adaptive method of extraction of non-stationary sinusoids is presented. Performance of the proposed method is demonstrated with the aid of computer simulations. Comparison is made between the proposed technique and existing methods. The proposed method features structural simplicity which renders it particularly attractive for implementation on software (MATLAB). It offers a high degree of immunity with regard to background noise and parameter variations. Compared to conventional methods, the proposed method offers a shorter measurement time which is of significant value. The purpose of developing this technique is to improve on already existing methods in the amount of time required for a subject to undergo the test, as well as the need for sound-proof environments. The basis of this technique is an algorithm, which is effective in extracting sinusoids from noise. The algorithm is found to be extremely robust with respect to both changes in internal parameters and fluctuations in external conditions. Combining this algorithm with some supportive signal processing modules, such as band-pass filters, allows for a quick and effective means to test the auditory response by attempting to extract a low-level sinusoid known as the distortion product otoacoustic emission (DPOAE). The development of the real-time application begins with digitizing and codifying the continuous model in the MATLAB environment. It is observed that this method of DPOAE estimation outperforms other linear estimation techniques, including the discrete Fourier transform (DFT). It offers a high degree of noise immunity while providing relatively faster measurements.
Keywords: Discrete Fourier Transform; Time Gating; Filter Design; Transient Evoked Otoacoustic Emissions